A label-free aptasensor for rapid detection of clenbuterol based on SYBR Green I. (5th August 2022) - Xiao, Shuyan; Sun, Liang; Lu, Jiping; Dong, Zhongping
Abstract : A label-free fluorescent aptasensor was constructed using aptamer as recognition element and SYBR Green I as signal reporter. Abstract : A label-free fluorescent biosensor based on the clenbuterol binding aptamer and the fluorescent intercalator SYBR Green I (SGI) was established for the sensitive and selective detection of clenbuterol. In the absence of clenbuterol, a weak fluorescence signal of SGI was observed. In the presence of clenbuterol, the specific recognition and high-affinity binding of the aptamer with clenbuterol induced a conformational change of the aptamer, and a longer double-stranded DNA was formed. As a result, an enhancement in the fluorescence of SGI could be found. Under optimal conditions, the fluorescence change ratio increased linearly with clenbuterol concentration from 50 nM to 450 nM, with a detection limit of 18.8 nM. In addition, the proposed aptasensor showed good selectivity and was successfully applied for clenbuterol quantification in pork samples with recoveries of 90.37–104.98%.